Distinct roles of XRCC4 and Ku80 in non-homologous end-joining of endonuclease- and ionizing radiation-induced DNA double-strand breaks - Schulte-Uentrop, Leonie (Oxford University Press, 2008)
Non-homologous end-joining (NHEJ) of DNA double-strand breaks (DSBs) is mediated by two protein complexes comprising Ku80/Ku70/DNA-PKcs/Artemis and XRCC4/LigaseIV/XLF. Loss of Ku or XRCC4/LigaseIV function compromises the rejoining of radiation-induced DSBs and leads to defective V(D)J recombination. In this study, we sought to define how XRCC4 and Ku80 affect NHEJ of site-directed chromosomal DSBs in murine fibroblasts. We employed a recently developed reporter system based on the rejoining of I-SceI endonuclease-induced DSBs. We found that the frequency of NHEJ was reduced by more than 20-fold in XRCC4−/− compared to XRCC4+/+ cells, while a Ku80 knock-out reduced the rejoining efficiency by only 1.4-fold. In contrast, lack of either XRCC4 or Ku80 increased end degradation and shifted repair towards a mode that used longer terminal microhomologies for rejoining. However, both proteins proved to be essential for the repair of radiation-induced DSBs. The remarkably different phenotype of XRCC4- and Ku80-deficient cells with regard to the repair of enzyme-induced DSBs mirrors the embryonic lethality of XRCC4 knock-out mice as opposed to the viability of the Ku80 knock-out. Thus, I-SceI-induced breaks may resemble DSBs arising during normal DNA metabolism and mouse development. The removal of these breaks likely has different genetic requirements than the repair of radiation-induced DSBs.